BRS A702 CL: new early-maturing irrigated rice cultivar with herbicide tolerance - Rangel,Paulo Hideo Nakano (2018)
Abstract The early-maturing irrigated rice cultivar BRS A702 CL was developed by Embrapa in partnership with BASF for the Clearfield Production System of irrigated rice in the tropical region of Brazil. In the states of Tocantins and Roraima, BRS A702 CL produces a mean yield of 7,650 kg ha-1.